(untitled) (2015)
The purpose of the present paper is the identification of value elements during the development of an interactive software, which is proposed for children with learning and development difficulties. In order to identify value elements the Systemic Archetype of co-creation is used, those values are identified by using a phenomenological analysis focused on experience of the co-creation network beneficiaries. The study comprises a previous phenomenological analysis of children's needs within their natural environment with parents and educators. The initial focus is the use case in the scenario that a child faces when going to the bathroom, identifying value elements for aural and graphic stimuli, then registered in software and used in the design phase. Results show the methodology allows the capture of value elements that express functional and no functional requirements, through qualifying speech acts with the purpose of design and develop software that could be redesigned in a co-created way with key actors using the service.